The Effects of Oil and Non-oil Exports on Economic Growth in Bahrain - Khayati, Anis (International Journal of Energy Economics and Policy, 2019)
This study investigates the effect of oil and non-oil exports on economic growth in Bahrain over the period 1977-2015. The cointegration analysis shows that economic growth was positively and significantly related to exports. However, oil effects have the biggest effect on real GDP. Also, results show that oil exports have a positive impact on economic growth both in the short run and in the long run. Therefore, further encouragement of non-oil sectors and higher diversification of exports would lead to positive effects on the economy. Keywords: economic growth, oil exports, causality, Bahrain JEL Classifications: F11, N15, O40 DOI: https://doi.org/10.32479/ijeep.7476